Occupation, prestige, and voluntary work in retirement: Empirical evidence from Germany - Holger Lengfeld; Jessica Ordemann (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
The paper examines the extent to which the prestige value of a retiree's former occupation increases the likelihood that they will make a transition into volunteering after retirement. Following social production function theory, we assume that when a person retires, the prestige value attached to their former occupation fades. The fact that volunteering has the character of a collective good provides the opportunity to gain social prestige to offset the loss of occupational prestige. However, the extent of the incentive to volunteer will be distributed unequally across occupations: the higher the former occupational prestige value, the higher the perceived loss of prestige after retirement. Thus, doing a job with high prestige value increases the incentive to volunteer in retirement. This assumption is tested, using data taken from the German Socio-Economic Panel (SOEP) 1992 - 2013. The sample contains 1,631 workers and 589 retirees, 278 of whom transitioned into volunteering during the observation window. Based on Kaplan-Meier-Failure-Estimates and complementary log-log hazard models, findings show a positive effect of occupational prestige on the transition into volunteering. Thus, the loss of high occupational prestige can be compensated by the social prestige associated with volunteering. Formal volunteering in retirement follows, albeit to a lesser extent, the logic of the occupational social strata.
Keywords: 330; Social Production Function Theory; Retirement; Volunteering; Occupations